In search of AKT kinase inhibitors as anticancer agents: structure-based design, docking, and molecular dynamics studies of 2, 4, 6-trisubstituted pyridines. Issue 2 (25th January 2018) - Trejo-Soto, Pedro Josué; Hernández-Campos, Alicia; Romo-Mancillas, Antonio; Medina-Franco, José L.; Castillo, Rafael
Abstract : The AKT isoforms are a group of key kinases that play a critical role in tumorigenesis. These enzymes are overexpressed in different types of cancers, such as breast, colon, prostate, ovarian, and lung. Because of its relevance the AKT isoforms are attractive targets for the design of anticancer molecules. However, it has been found that AKT1 and AKT3 isoforms have a main role in tumor progression and metastasis; thus, the identification of AKT isoforms specific inhibitors seems to be a challenge. Previously, we identified an ATP binding pocket pan-AKT inhibitor, this compound is a 2, 4, 6-trisubstituted pyridine (compound11 ), which represents a new interesting scaffold for the developing of AKT inhibitors. Starting from the 2, 4, 6-trisubstituted pyridine scaffold, and guided by structure-based design technique, 42 new inhibitors were designed and further evaluated in the three AKT isoforms by multiple docking approach and molecular dynamics. Results showed that seven compounds presented binding selectivity for AKT1 and AKT3, better than for AKT2. The binding affinities of these seven compounds on AKT1 and AKT3 isoforms were mainly determined by hydrophobic contributions between the aromatic portion at position 4 of the pyridine ring with residues Phe236/234, Phe237/235, Phe438/435, and Phe442/439 in the ATP binding pocket. Results presented in this work provide an addition knowledge leading to promising selective AKT inhibitors.